GaSb/GaAs Type-II Heterojunction TFET on SELBOX Substrate for Dielectric Modulated Label-Free Biosensing Application - Singh A.K.; Tripathy M.R.; Baral K.; Jit S. (My University, 2025)
A novel GaSb/GaAs type-II heterojunction TFET on SELBOX substrate (HJ-STFET)-based dielectric-modulated ultrasensitive label-free biosensor has been demonstrated in this article. The SELBOX substrate has been used in the proposed TFET-based sensor to reduce the lattice heat and improve the ION/IOFF ratio. Cavities in the gate oxide of the TFET are created to form dual-cavity (DC) HJ-STFET structure. These cavities contain the biomolecules to be sensed through the principle of gate-dielectric modulation. To validate the results, the analytical modeling of surface potential has been compared to simulated outcomes for different dielectric constant values of biomolecules. The threshold voltage sensitivity (SVT) and ION/IOFF sensitivity parameters of the proposed DC-HJ-STFET structure have been thoroughly investigated considering different biomolecules. The proposed DC-HJ-TFET structure is shown to have a higher current sensitivity (~6.67×1011) and threshold voltage sensitivity (0.37 V) values over some recently reported TFET-based biosensors. Finally, we have verified the drain and back gate biasing, as well as linearity fit verification, on the proposed biosensor's performance. © 1963-2012 IEEE.